Association Between Exercise Therapy Dose and Functional Improvements in the Early Postoperative Phase After Hip and Knee Arthroplasty: An Observational Study. Issue 10 (16th April 2015) - Zech, Astrid; Hendrich, Simon; Pfeifer, Klaus
Abstract: Objective: To determine whether intensity and duration of standard exercise therapy are associated with changes in function after total hip arthroplasty (THA) and total knee arthroplasty (TKA). Design: Prospective cohort study. Setting: Orthopedic inpatient rehabilitation center. Participants: A total of 123 patients 2 weeks after THA (n = 58; age, 62.5 ± 10.4 years) and TKA (n = 65; age, 66.6 ± 7.6 years). Intervention: Standard rehabilitation (hands‐on physiotherapy, group exercise therapy, strength training, cycle ergometer therapy, continuous passive motion therapy, and water exercise therapy). Main Outcome Measures: The Western Ontario and McMaster Universities Arthritis Index (WOMAC) and hip and knee range of motion (ROM) were assessed before and after inpatient rehabilitation. Results: The individual rehabilitation period varied between 12‐25 days and included 48.1 ± 12.5 (THA) or 41.9 ± 9.7 (TKA) exercise interventions with intensities between 9.6 and 14.0 points on the Borg Rate of Perceived Exertion Scale. WOMAC pain ( P < .001), stiffness ( P < .001), and function ( P < .001), as well as hip ( P < .001) and knee ( P < .001) ROM, improved significantly in THA and TKA patients. Analysis of covariance showed that these changes could not be explained by the total duration or mean intensity of exercise therapy. Conclusions: The findings show a low dose‐response relationship between early postoperative exercise therapy and the improvements in function or ROM after THA and TKA. Although the findings raise questions about the efficacy of existing rehabilitation programs, the small sample size, single setting, and geographic differences in postoperative treatment standards limit the generalizability of findings.